Considering the direction of innovation in EU merger control - Juliane Mendelsohn; Lukas Breide (Journal of Responsible Innovation, 2024)
This paper considers the role that innovation plays in EU merger control analysis, and seeks to integrate perspectives highlighted by the philosophical literature on the so-called ‘direction of innovation’ in order to critically assess the impact of market concentration on the diversity of innovation and its ability to address larger normative questions and challenges, such as the transition to more sustainable economies. While normative goals other than competition are not an inherent part of merger control, this paper argues that in concentrated markets, ignoring such questions can play into the hands of the powerful merging entities, allowing them to further determine the direction of innovation to best serve their interests and business models rather than public interests. This is illustrated by critically discussing the merger between Bayer and Monsanto as an example.